Electrochemical behavior and magnetic properties of vanadium oxide nanotubes - Popa, Andreia Ioana; Vavilova, Evgenia; Täschner, Christine; Kataev, Vladislav; Büchner, Bernd; Klingeler, Rüdiger (The journal of physical chemistry. C, Energy, materials, and catalysis, 2011)
The electrochemical behavior and magnetic properties of electrochemically lithium-doped mixed valence vanadium oxide nanotubes (VOx-NTs) have been studied. The materials were synthesized hydrothermally. Primary amines (CH3−(CH2)11−NH2) were used as spacer molecules aiding to retain the nanotubular shape of the VOx layers. Cyclic voltammograms and potentiostatic measurements indicate that the electrochemical behavior of this material is fairly sensitive to the preparation conditions. Specific capacity values for this material are higher than similar template VOx-NTs. Lithium doping level of x = 0.1 in two different VOx-NTs gives rise to room-temperature ferromagnetism in LixVOx-NTs.
Gesehen am 05.01.2023